CHARACTERISTICS OF CREATIVITY AND INNOVATIVENESS MANIFESTATIONS IN STUDENTS OF MIDDLE AHD HIGH SCHOOL - Mikhailova, O.В. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2017)
The development of a young person’s potential capabilities is one of the important directions in the modern practicing psychologists’ activity. The absence of a scientifically motivated way of analyzing the innovation potential development in a personality and the formation of principles and methods regulating its progress allowed to formulate the aim of the research, which is to work out a technology of innovation potential development and self-realisation in a personality on the basis of empirical investigations. The technology is to forward the introduction of a system of theoretical and practical basics for the innovation potential evolution in different periods of personal development.The distinctive peculiarity of the given article is the integration of psychological and pedagogical approaches to analyzing the preconditions of basic creativity and innovativeness development in a personality in secondary school educational environment. As a result of the study we analyzed the qualitative and quantitative information about the features of the innovative behavior and creativity in the students of 13-14 years old and students of 16-18 years old.The interpretation of the numerous data suggests that there are significant differences in the features of creativity and innovativeness in the students of different ages. Based on the results, the article presents the recommendations for the improvement of psychological and pedagogical technologies that accompany the formation of the innovative potential of a personality in middle and high school.